Experimental Therapeutics in the Treatment of COVID-19 – Infection by SARS-CoV-2 - de Farmacoterapia, Revista Portuguesa (2020)
In March 2020, INFARMED, I.P., published two documents «Guidelines for Access to Experimental Therapeutics in the treatment of COVID-19 – infection by SARS-CoV-2» and «Experimental Therapeutics in the treatment of COVID-19 – infection by SARS-CoV-2”, which are based on information available from the European Medicines Agency, European Centre for Disease Prevention and Control, World Health Organization and other sources on the subject. This section seeks to describe a brief summary of both documents. Available in: https://www.infarmed.pt/documents/15786/3584301/Orienta%C3%A7%C3%B5es+de+Acesso+a+Terap%C3%AAuticas+Experimentais+no+tratamento+de+COVID-19+-+infe%C3%A7%C3%A3o+pelo+SARS-CoV-2/c9595d6a-6a2f-255d-1f45-668b20db0ed6 and https://www.infarmed.pt/documents/15786/3584301/Terap%C3%AAuticas+Experimentais+no+tratamento+de+COVID-19+%C2%BFinfe%C3%A7%C3%A3o+pelo+SARS-CoV-2/5f8f5e54-e482-31f3-3b8a-ff862fe96dd9.